Research on the Relationship Between Strategic Difference Degree and Innovation Performance - Zeng, Hongxia; Tang, Long (International Journal of Global Economics and Management, 2024)
In the era of knowledge economy, the marginal contribution of knowledge to innovation exceeds that of traditional material production factors. The advantage of technological innovation of enterprises is more due to the change of managers’ cognition, rather than determined by heterogeneous resources. Innovation is the key driving force to achieve sustainable competitive advantage, and strategic choice is one of the important factors affecting innovation performance. This paper aims to explore the mechanism of the impact of strategic variance on innovation performance, enrich the research on the impact of strategic variance on innovation performance, and provide countermeasures and suggestions for enterprises to realize transformation and upgrading through strategic planning and make full use of financial advantages to improve innovation performance.